Prioritisation of Informed Health Choices (IHC) key concepts to be included in lower secondary school resources: A consensus study - Agaba, Joseph Jude; Mugisha, Michael; Nsangi, Allen; Oxman, Andrew David (PLoS One, 2023)
The Informed Health Choices Key Concepts are principles for thinking critically about healthcare claims and deciding what to do. The Key Concepts provide a framework for designing curricula, learning resources, and evaluation tools.